2013
DOI: 10.3233/npm-1364112
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines patterns in newborn infants with late onset sepsis

Abstract: BACKGROUND: Cytokines might be helpful to diagnose late onset sepsis (LOS) in newborn infants. Many studies on cytokines did not discriminate culture-proven from clinically-suspected sepsis; however, such differentiation is clinically useful. OBJECTIVES: To evaluate the feasibility to differentiate among culture-proven LOS, clinical LOS and controls using a battery of cytokines. STUDY DESIGN: This prospective study was conducted at the NICU of Harapan-Kita Women and Children's Hospital, Jakarta-Indonesia. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 37 publications
0
24
0
15
Order By: Relevance
“…Inflammatory mediators of systemic inflammation, including cytokines interferon gamma (IFNγ), interleukin (IL) 1, IL‐6, IL‐18, IL‐2 and IL‐10, and chemokines IL‐8 and monocyte chemotactic protein 1 (MCP1), are upregulated in human neonatal sepsis . Though cytokines are known to be predictive of early sepsis in other neonatal species , there is limited knowledge of the foal host response to events and disease in early life.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory mediators of systemic inflammation, including cytokines interferon gamma (IFNγ), interleukin (IL) 1, IL‐6, IL‐18, IL‐2 and IL‐10, and chemokines IL‐8 and monocyte chemotactic protein 1 (MCP1), are upregulated in human neonatal sepsis . Though cytokines are known to be predictive of early sepsis in other neonatal species , there is limited knowledge of the foal host response to events and disease in early life.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies have reported that IL-6 shows great promise as a biomarker [60][61][62][63]. Like TNF and IL-1b, IL-6 is not altered only in sepsis; nevertheless, several studies have shown its importance in the prognosis of sepsis presenting strong correlations with patient mortality [62,63]. These results were also shown in an animal model of acute septic peritonitis (CLP) [61].…”
Section: Cytokines As Biomarkersmentioning
confidence: 99%
“…In preterm infants, the reserve pool of granulocytes is smaller, and may be depleted faster than in full-term infants. The ability to accelerate the maturation of granulocytes is also reduced, which creates the risk of developing severe infections with poor prognosis [10,11,12,13]. It is believed, that in the early phase of inflammation, cytokine-induced leukocyte activation changes the expression of many adhesion molecules on the surface of granulocytes and monocytes.…”
Section: Introductionmentioning
confidence: 99%
“…U wcześniaków pula rezerwowa granulocytów jest mniejsza i może ulec szybszemu wyczerpaniu niż u noworodków donoszonych. Obniżona jest również zdolność przyspieszenia dojrzewania granulocytów w szpiku, co wiąże się z ryzykiem rozwoju zakażeń o ciężkim przebiegu i niepomyślnym rokowaniu [10,11,12,13]. Uważa się, że we wczesnej fazie zapalenia następuje aktywacja leukocytów indukowana cytokinami, co powoduje zmiany ekspresji wielu molekuł adhezyjnych na powierzchni granulocytów i monocytów.…”
Section: Introductionunclassified